2005
DOI: 10.1097/01.hjh.0000163140.82212.16
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and aortic stiffness in young men and women

Abstract: Background Moderate alcohol consumption has been shown to protect against cardiovascular disease. Aortic stiffness can be regarded as a marker of cardiovascular disease risk. Previously we have shown an inverse to Jshaped association between alcohol intake and aortic stiffness in middle-aged and elderly men and postmenopausal women.Objective In the present study we examined whether a relation between alcohol intake and aortic stiffness is already present at a younger age.Design Cross-sectional data of a cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
16
1
1
Order By: Relevance
“…These findings contrast with those reported in middleaged Japanese men [22]. van den Elzen et al [19] now report an inverse association between alcohol consumption and vascular stiffness in young women but not in young men. A number of issues arise from their study.…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…These findings contrast with those reported in middleaged Japanese men [22]. van den Elzen et al [19] now report an inverse association between alcohol consumption and vascular stiffness in young women but not in young men. A number of issues arise from their study.…”
contrasting
confidence: 61%
“…In the context of cardioprotection, in this issue of the journal, van den Elzen et al [19] address the possible beneficial effects of light to moderate drinking on vascular stiffness in 524 healthy young Dutch adults. The authors have previously reported that regular light to moderate alcohol consumption is associated with decreased aortic stiffness in men and postmenopausal women aged over 40 years, as assessed by pulse wave velocity from the carotid to femoral arteries [20,21].…”
mentioning
confidence: 98%
“…Cross-sectional data from Holland described an inverse or J-shaped relation between alcohol intake and measures of aortic stiffness in middle-aged and older men and pre-and postmenopausal women 13,14 but not in younger men. 15 They recognized that these results might be confounded by other lifestyle factors but suggested that if they were causally linked direct effects of alcohol to improve vascular compliance might contribute to any cardioprotective effect.…”
Section: Effects On Large Vessel Structure and Functionmentioning
confidence: 99%
“…Subjects who smoked were not excluded from the study but were asked to refrain from smoking for 24 h (34,35). Similarly, subjects were required to abstain from coffee (34) and alcohol (33) for Ն12 h before the study. Subjects were not studied within 9 h of eating.…”
Section: Precatheterizationmentioning
confidence: 99%